A Novel Technique for Pedicled Nasoseptal Flap Takedown in Revision Skull Base Surgery - Nation, Javan J.; Shkoukani, Mahdi; Guthikonda, Murali; Folbe, Adam J. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To describe a novel technique of using the CO2 laser for a revision pedicled nasoseptal flap (PNSF) takedown.Patient Patient with a pituitary adenoma recurrence that had undergone an endoscopic skull base resection with a nasoseptal flap repair 3 years prior.Procedure Flap edges and bony defect are examined using an image-guidance probe to identify the full extent of the defect. The CO2 laser fiber is used to incise through to the underlying skull base. The flap is then elevated from its most distal portion toward the pedicle, using the laser to cut adhesions away from the underlying dura. The skull base defect is then repaired with an onlay graft of acellular dermis, then the PNSF.Results The laser was adept at dissecting through mucosa to the underlying bone and at dissecting the underside of the flap from the posterior adhesions and intradural structures safely.Conclusion The novel use of the of the CO2 laser for the flap takedown was very effective at safely making the mucosal cuts and dissecting the flap from the underlying structures. The nasoseptal flap takedown can be a technically challenging procedure that was made easier by the use of the CO2 laser.
Keywords: pedicled nasoseptal flap; anterior skull base surgery; CO2 laser; novel; revision; takedown